2022
DOI: 10.3389/feart.2022.930474
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Characterization Techniques for Shale Reservoirs: A Review

Abstract: The microstructure of shale reservoirs refers to the distribution of mineral–organic matter, pore–fracture features, diagenetic processes, and their interrelations. The comprehensive and accurate analysis of the shale microstructure plays a critical role in formulating a reasonable development plan and optimizing measures to enhance oil or gas recovery. To explore the microstructure characterization, the mineral and organic matter compositions as well as the pore types and distributions of organic-rich shale r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Sand production can lead to problems such as reduced reservoir permeability and equipment damage. Chemical sand control methods can improve reservoir stability and effectively prevent SEM working principle and SEM image (A), CT working principle and CT image (B) (Lai et al, 2018;Qian et al, 2022;Liu et al, 2023).…”
Section: Conclusion Challenges and Prospectsmentioning
confidence: 99%
“…Sand production can lead to problems such as reduced reservoir permeability and equipment damage. Chemical sand control methods can improve reservoir stability and effectively prevent SEM working principle and SEM image (A), CT working principle and CT image (B) (Lai et al, 2018;Qian et al, 2022;Liu et al, 2023).…”
Section: Conclusion Challenges and Prospectsmentioning
confidence: 99%
“…On one hand, fractures play a role in connecting oil and gas and increasing reservoir permeability; On the other hand, fractures may cause casing deformation, inter-well frachit and other accidents. Therefore, identifying and evaluating the fractures near the well, especially the fractures intersected with the well bore, has guiding significance for formulating reasonable development and production planning for unconventional reservoirs (Cai et al, 2022a;Cai et al, 2022b;Qian et al, 2022). At present, the unconventional reservoir fracture logging evaluation method is difficult to meet the field demand, especially in highly deviated wells and horizontal wells.…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing demand for unconventional resources, shale oil exploration has become increasingly important . Shale reservoirs contain numerous micron-sized pores and nanosized pores. , Previous studies have shown that the interactions among fluids are dominant in some larger pores, while the fluid is obviously influenced by the surface in smaller pores, which cause great differences in the physical and chemical properties of shale oil and contributes to diverse occurrence states, , which in turn increases the difficulty of exploration and production . Thus, probing the relationship between the pore and surface is of great significance to identify sweet spots and enhance shale oil recovery.…”
Section: Introductionmentioning
confidence: 99%